Pengaruh Sinar Ultraviolet Terhadap Jamur Aspergillus Niger - Ayu Ratnawati, I Gusti Agung; Putra, I Ketut; Suryatika, Ida Bagus Made; Sutapa, Gusti Ngurah; Trisnawati, Ni Luh Putu (Universitas Hamzanwadi, 2023)
Along with the development of science and technology, some researchers try to apply knowledge to several biological systems to obtain benefits that can be used. One of them is the use of ultraviolet light to kill the fungus Aspergillus niger. In addition, ultraviolet rays are also used in various fields of the drinking water industry, food, and also for sterilizing operating rooms in hospitals. A method used in this problem is the cork borer method. Data were obtained by measuring the diameter of the inhibition zone of the Aspergillus niger fungus. The results of this study were obtained at the intensity of 12.30 lux and at a distance of 15cm, within 15 minutes of irradiation time, the maximum death of the fungus Aspergillus niger was 40.74%.